A Construction of Students' National Insight in Tiktok Social Media as a Form of Increasing Digital Literacy at Smpn 12 Bandung - septiani dwi; Sapriya; Dwi Iman Muthaqin (The International Journal of Education Management and Sociology, 2025)
Based on cases that occur among junior high school students, there is a decline in students' national insight which is caused by the lack of digital literacy in using TikTok social media. This can damage the nation's morals so that it can hinder the nation's ideals in accordance with the opening of the 1945 Constitution which is a guideline for all Indonesian people. This study aims to determine how students' use of TikTok social media in building national insight and increasing students' digital literacy. This study uses a qualitative descriptive approach implemented in the junior high school 12, Bandung. The results of the study show that the use of social media in building national insight has an important influence on improving students' digital literacy. By internalizing two aspects of national insight and good digital literacy, students are expected to have intellectual, emotional, social, and spiritual intelligence as well as a sense of love for the homeland and a responsible attitude that is able to play a role in community, national, and state life. This research needs to be carried out in order to foster a sense of nationalism in students with good digital literacy. With this, students' national insight and digital literacy will always be embedded in the souls of students and their every behavior so that they are not swept away by the current of globalization.